Evolution of the conductivity type in germania by varying the stoichiometry - Islamov, D. R.; Gritsenko, V. A.; Cheng, C. H.; Chin, A. (My University, 2013)
Information regarding the conductivity type of Si/GeOx/Ni structures with various stoichiometry has been obtained using experiments on injection of minority carriers from n- and p-type silicon. Results show that non-stoichiometric GeOx films exhibit bipolar conductivity, that is, holes as well as electrons contribute to the charge transport. Stoichiometric GeO2 films exhibit unipolar electron conductivity. (C) 2013 AIP Publishing LLC.